Coaching Clinic Mahasiswa Poltekkes Mataram untuk National Health English Olympiade - Husnawadi; Suhendra, Erwin; Abdul Muhid (Insan Kreasi Media, 2023)
This coaching clinic is aimed to give assistance, guidance, and coaching to the public speaking competition on NHPEO, which are: public speaking, storytelling, English debate, and writing essays. This competition is held annually for Health Polytechnic all over Indonesia. This coaching clinic is programmed into two approaches; assisting and coaching. Preceding the programs, a pre-test was given to measure students' competence, and a post-test was given to decide the selected team for NHPEO. This coaching clinic is followed by selected students of Poltekkes Kemenkes Mataram. The activities are programmed for three months and conducted through the collaboration of Universitas Bumigora, Poltekkes Kemenkes Mataram, and TESLA Language Institute. The outcome of this coaching clinic was students’ better understanding of technical strategies to construct; speeches, stories, argumentations and writings. Further, students have better confidence during the performance of public speaking.